Digital Zakat Literacy: Synergy of Religious Values and Technology from the Utaut Perspective - Khansa Shabihah; Dedi Rusdi; Amnisuhailah Abarahan; Tazkiya Nafsa Ramadhani (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: As digital technology becomes increasingly embedded in daily life, its influence extends into faith-based and philanthropic activities among Muslim communities, particularly through the development of digital zakat services. This study investigates whether technology-related factors (performance expectancy, effort expectancy, social influence, facilitating conditions) and institutional as well as personal factors (transparency, accountability, religiosity) affect the intention to participate in digital zakat systems. Method: The findings show that transparency (B = 0.156; p = 0.007) and accountability (B = 0.416; p < 0.001) have a positive and significant effect on the intention to use digital zakat services. Meanwhile, religiosity (B = -0.001; p = 0.977) does not have a significant effect. Conclusion: Institutional trust, reflected through transparency and accountability, plays a more important role in encouraging the use of digital zakat platforms than individual religiosity. Therefore, zakat management institutions should focus on improving transparency, accountability, and system reliability to increase public participation.